Nutritional Status of Pregnant Women and History Parity for Stunting in Toddler Ages 24-59 - Lidyani Margareth; Nurul Husnul Lail; Lisa Trina Arlym (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting is a condition where a child experiences growth disorders, which results in the child's height not being appropriate for his age as a result of chronic nutritional problems, namely a lack of adequate nutritional intake over a long period of time. Objective to analyze the relationship between maternal risk factors and the incidence of stunting among toddlers in the Karawaci Health Center working area. This research design uses an observational analytical quantitative research type with a case control design. The case samples in this study were toddlers aged 24-59 months who experienced stunting with a TB/U toddler Z score < -2 SD and the data was recorded at the Karawaci Health Center in 2023 as many as 123 toddlers, and a control sample of 123 toddlers. Data were analyzed using the chi square statistical test. Results of bivariate analysis Overall, of the 11 variables carried out in the research, 5 of them showed a relationship between these variables and the incidence of stunting in toddlers, including a relationship between parity, of stunting. in toddlers aged 24-59 months who are in the working area of the Karawaci Health Center.There is no relationship between the nutritional status of pregnant women, with the incidence of stunting in toddlers aged 24-59 months in the working area of the Karawaci Health Center. And the factor that poses the greatest risk for stunting is the age of the mother at risk during pregnancy, where stunting is 3.42 times more likely to occur than mothers of normal age during pregnancy. There is a relationship between the number of parities, maternal age at pregnancy, history of anemia during pregnancy, birth interval and maternal education level with the incidence of stunting.